1992
DOI: 10.1002/jcu.1870200810
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the native kidney in dialysis and transplant patients

Abstract: The native kidneys in patients on dialysis or after transplantation tend to be overlooked until problems occur in relation to them. Their appearance can be variable and does not bear any consistent relationship to the cause of the renal failure; although in some cases, such as polycystic kidney disease, there are specific changes to be seen. Size can also be variable with little correlation to pathology in most cases. Acquired cystic disease of the kidneys is seen in up to 92% of long-term dialysis patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…However, only a few reports are there on the study of the actual decrease rate [2–4]. On the other hand, scheduled ultrasonographic (US) examination of kidney after induction of HD is important to check the progression of acquired cystic disease of kidney (ACDK) and renal cancer which may arise in ACDK [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few reports are there on the study of the actual decrease rate [2–4]. On the other hand, scheduled ultrasonographic (US) examination of kidney after induction of HD is important to check the progression of acquired cystic disease of kidney (ACDK) and renal cancer which may arise in ACDK [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…A DRCA pode, eventualmente, trazer como complicação cistos hemorrágicos 10 , hemorragia retroperitoneal 11 e carcinoma renal 6,7,[11][12][13][14] que aumentam a morbidade e a mortalidade dessa doença.…”
Section: Introductionunclassified
“…Renal transplantation is the most effective treatment option in patients with end-stage renal disease. Studies have shown that the 5-year survival after renal transplantation is 70%, as compared to 30% survival in patients receiving dialysis ( 1 ). The use of appropriate diagnostic method in preoperative analysis but also in postoperative follow up protocol is necessary for accurate preparation and early diagnosis of complications and workflow efficiency ( 2 ).…”
mentioning
confidence: 99%